Muonic atom formation processes for carbon containing molecules. (July 2015) - Yoshida, Go; Ninomiya, Kazuhiko; Inagaki, Makoto; Higemoto, Wataru; Ito, Takashi U; Kawamura, Naritoshi; Shimomura, Kohichiro; Miyake, Yasuhiro; Miura, Taichi; Kubo, Kenya M; Shinohara, Atsushi
Synopsis: Muonic atom is an atomic system which has a negative muon substituted an electron. Muonic atom formation processes are strongly influenced by the chemical environment of muon capturing atom such as molecular structure, however, the initial processes of muon capture still have not been well investigated. In this study, we performed muon irradiation for gaseous carbon containing molecules to investigate the chemical environmental effect on muon capture processes.